Media And Cultural Heritage - Inge Hutagalung (Lembaga Penelitian Universitas Pasundan, 2015)
In general, media coverage can have a strong influence on the reputation of a cultural heritage. Media coverage often has an effect on a cultural heritage’s reputation when ‘good’ or ‘bad’ news is reported.This amplifying effect has often been studied through the lens of agenda setting theory. The hypothesis behind the theory is that the frequency with the media report on an issue determines that issues’ salience in the minds of the general public. In other words, the media may not be successful often time in telling people what to think, but it is stunningly successful in telling its readers what to think about. The news media ‘set’ the public agenda.Since people cannot possibly attend no to every little detail about the cultural heritage around them, setting in communication is important because it helps shape the perspectives through which people see all cultural heritage in the world.In generating good news coverage about a cultural heritage, communicating with the media is one of important activities that should be maintained between communication professionals (in cultural heritage) with journalists. Keywords: media coverage, agenda setting, framing news